2007
DOI: 10.1152/ajprenal.00458.2005
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 as a flow sensor in flow-dependent K+ secretion from the cortical collecting duct

Abstract: The transient receptor vanilloid-4 (TRPV4) is a mechanosensitive, swell-activated cation channel that is abundant in the renal distal tubules. Immunolocalization studies, however, present conflicting data as to whether TRPV4 is expressed along the apical and/or basolateral membranes. To disclose the role of TRPV4 in flow-dependent K(+) secretion in distal tubules in vivo, urinary K(+) excretion and net transports of K(+) and Na(+) in the cortical collecting duct (CCD) were measured with an in vitro microperfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 30 publications
(45 reference statements)
6
91
0
Order By: Relevance
“…Indeed, our group recently demonstrated that genetic ablation of TRPV4 abolishes flow-dependent [Ca 2ϩ ] i responses in microdissected distal nephron preparations (12). Consistently, flow-dependent K ϩ secretion in the distal nephron, a Ca 2ϩ -dependent process utilizing the maxi-K channel (13,14), is absent in TRPV4 knock-out animals (15).…”
Section: ؉mentioning
confidence: 87%
See 1 more Smart Citation
“…Indeed, our group recently demonstrated that genetic ablation of TRPV4 abolishes flow-dependent [Ca 2ϩ ] i responses in microdissected distal nephron preparations (12). Consistently, flow-dependent K ϩ secretion in the distal nephron, a Ca 2ϩ -dependent process utilizing the maxi-K channel (13,14), is absent in TRPV4 knock-out animals (15).…”
Section: ؉mentioning
confidence: 87%
“…Adequate mechanosensitive [Ca 2ϩ ] i responses are important determinants of many physiological processes in late nephron segments, including flow-dependent K ϩ secretion (15,25), regulatory volume decreases (26), etc. Furthermore, we and others have recently demonstrated that pharmacological stimulation of TRPV4 activity is instrumental for blunting renal cystogenesis in ARPKD models (18,27).…”
Section: Discussionmentioning
confidence: 99%
“…These candidate channels include TRPV4, 7,8 TRPP1-P2 complex, 9 heteromeric TRPV4-P2, 10 and heteromeric TRPV4-C1. 11 Our coimmunoprecipitation and double immunostaining experiments showed the physical association of TRPV4 and TRPP2.…”
Section: Discussionmentioning
confidence: 99%
“…2,6 There is intense interest in searching for the plasma membrane channels that mediate flow-induced Ca 2+ entry in renal epithelial cells. Several candidate channels have been proposed, including transient receptor potential vanilloid 4 (TRPV4), 7,8 transient receptor potential polycystin 1 (TRPP1)-TRPP2 complex, 9 and heteromeric TRPV4-P2 channels. 10 It is suggested that TRPP1 and TRPP2 may form a physical complex in which TRPP1 serves as a sensor to transduce the flow stimuli to TRPP2, which is a Ca 2+ entry channel.…”
mentioning
confidence: 99%
“…TRPV4 participation in osmo-and mechanotransduction (1,2) contributes to important functions including cellular (3,4) and systemic volume homeostasis (5,6), arterial dilation (7,8), nociception (9), epithelial hydroelectrolyte transport (10,11), bladder voiding (12), and ciliary beat frequency regulation (13)(14)(15). TRPV4 also responds to temperature (16,17), endogenous arachidonic acid (AA) metabolites (18), and phorbol esters including the inactive 4␣-phorbol 12,13-didecanoate (4␣PDD) (19,20) and participates in receptor-operated Ca 2ϩ entry (15), thus showing multiple modes of activation.…”
Section: The Trpv4mentioning
confidence: 99%